A new furileusaurian abelisaurid from La Invernada (Upper Cretaceous, Santonian, Bajo de la Carpa Formation), northern Patagonia, Argentina. Issue 6 (10th December 2020) - Gianechini, Federico A.; Méndez, Ariel H.; Filippi, Leonardo S.; Paulina-Carabajal, Ariana; Juárez-Valieri, Rubén D.; Garrido, Alberto C.
ABSTRACT: Abelisaurids are among the most abundant and diverse Patagonian Late Cretaceous theropods. Here, we present a new furileusaurian abelisaurid, Llukalkan aliocranianus gen. et sp. nov., represented by cranial remains from the Bajo de la Carpa Formation (Santonian) at La Invernada fossil area, northwestern Patagonia. Features characterizing this taxon include a possible caudal tympanic recess posterior to the columellar recess, a T-shaped lacrimal with jugal ramus lacking a suborbital process, and large foramina for caudal middle cerebral veins widely separated from the median supraoccipital crest. In addition to this, a bulge on the anteromedial border of the supratemporal fossa, tall and posteriorly projected paroccipital processes, basal tubera interconnected distally, a triangular basisphenoid recess, and a single foramen for the sphenoidal artery on the basisphenoid, differentiate Llukalkan from Viavenator exxoni . The latter is the other furileusaurian taxon from the same area and stratigraphic unit. Although the holotype of Llukalkan probably corresponds to a sub-adult—as the lacrimal morphology suggests— the possibility that it represents a juvenile of V. exxoni is discarded based mainly on the presence of a caudal tympanic recess (which is absent in V. exxoni ). The probable coexistence of two abelisaurid taxa demonstrates that the abelisaurids were one of the most important—and likely the main—predator component of the ecosystems, not only in this area, but also in all of Patagonia, during the Late Cretaceous.